(untitled) (American Journal of Pedagogical and Educational Research, 2023)
An original solution for the removal of completely missing teeth with intolerance to acrylic prostheses is presented. A reinforced full removable prosthesis made of polypropylene has been developed. Clinical trials have shown the advantages of the proposed method in comparison with the most common similar products.